NEW PARADIGM OF THE EUROPEAN URBAN AREA DUE TO ECONOMIC GLOBALIZATION AND TECHNOLOGICAL REVOLUTION - vana VYSLUZILOVA (European Journal of Geography)
The paper concerns what influences possess rapid growing significance of technological information on a global scale. The focus is on the role of urban structures in Europe. Economic globalization declares the increasing interdependence of world economies and is largely based on the accelerated development of science and information technologies. Therein, IT development is investigated as a strong technological driving force for economic globalization and reduction of global connection barriers. The conceptual bases for the development of strategic global cities in international trade are examined. The impact of technology on the transformation of modern society are examined as well. The application of modern mechanisms innovation development of the economy is justified. Nevertheless, this process can pose certain risks and have some limitations. Preconditions for the urban development of national economies in European urban areas are highlighted. The main conclusion is that the transition to modern and economically connected European urban areas can lead to new era supported by a technological revolution